2006
DOI: 10.7326/0003-4819-144-1-200601030-00006
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index and Risk for End-Stage Renal Disease

Abstract: High BMI is a common, strong, and potentially modifiable risk factor for ESRD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
690
6
30

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 1,188 publications
(782 citation statements)
references
References 40 publications
28
690
6
30
Order By: Relevance
“…Accumulating evidence indicates that higher BMI is a risk factor for CKD in apparently healthy persons [28, 29], and graft loss in kidney transplantation recipients [30]. The result of a recent study from Taiwan [31] also supports this notion.…”
Section: Discussionsupporting
confidence: 74%
“…Accumulating evidence indicates that higher BMI is a risk factor for CKD in apparently healthy persons [28, 29], and graft loss in kidney transplantation recipients [30]. The result of a recent study from Taiwan [31] also supports this notion.…”
Section: Discussionsupporting
confidence: 74%
“…No relation was found between renal size and body habitus and it was concluded that renal size was independent of BMI, which concurred with the studies carried out in the past [1,45]. Several researches reported that increased BMI was closely associated with the increased risk of developing chronic renal disease as well as ESRD (end stage renal disease) [48][49][50].…”
Section: Bmi Influencing the Renal Volumesupporting
confidence: 62%
“…Furthermore, in numerous large population-based studies, higher BMI appears associated with the presence 8,12 and development of low estimated glomerular filtration rate (GFR), 9,10,13 with more rapid loss of estimated GFR over time, 14 and with the incidence of ESRD. [15][16][17][18] Elevated BMI levels, class II obesity and above, have been associated with more rapid progression of CKD in patients with pre-existing CKD. 19 A few studies examining the association of abdominal obesity using WHR or WC with CKD, describe an association between higher girth and albuminuria, 20 Higher visceral adipose tissue measured by computed tomography has been associated with a higher prevalence of albuminuria in men.…”
Section: Association Of Obesity With Ckd and Other Renal Complicationsmentioning
confidence: 99%